Development of a Hybrid Anaerobic Bioreactor for Treatment and Energy Conversion of Organic Effluents - Shaji James, P; F, Mary Regina; JJL, Bovas; S, Kamaraj (JOURNAL OF ROOT CROPS, 2015)
Many agro-processing industries like cassava starch factories cause pollution of air and water due to the discharge of untreated organic effluents. Often, these industries face shortage of fuels for providing the process heat. Anaerobic treatment of agro-industrial effluents is an eco-friendly alternative for conversion of these liquid wastes to energy in the form of methane. Up-flow anaerobic hybrid reactors (UAHR) for treatment of cassava starch factory effluent (CSFE) were designed and fabricated with preprocessed coconut shells as media and was evaluated in comparison to another bioreactor with PVC pall rings media by operating the system at different hydraulic retention times (HRT). The performance of the bioreactors were found to be satisfactory in their ability for pollutant reduction and energy (biogas) production. Subsequently, similar lab scale bioreactors with coconut shells as well as rubber seed outer shells as media could be successfully used for Rice Mill Effluent (RME). Even though a slight inhibitory effect was observed in the case of coconut shells during the start-up the developed UAHR was found to be effective in pollutant reduction and energy conversion in the case of RME also. Based on these successful experiences, a pilot scale UAHR was installed for biomethanation of waste coconut water (WCW) from a coconut oil mill. The system was operated successfully for four months at a hydraulic retention time of five days. The cost reduction achieved by replacement of synthetic media with locally available natural materials as well as the simple design coupled with high treatment efficiency and biogas production ability offers great scope for energy conversion of these agro-industrial effluents.